Transgender youth and oral health: a qualitative study. Issue 1 (2nd January 2022) - Macdonald, David W.; Grossoehme, Daniel H.; Mazzola, Amanda; Pestian, Teresa; Schwartz, Scott B.
Abstract: Transgender youth face several comorbidities with oral health implications, including depression, harmful eating behaviors, and pharmaceutical side-effects. No information exists on how transgender youth view oral health or how they interface with oral health providers. The purpose of this study was to elicit experiences, knowledge, and perceptions of oral health among transgender youth and their caregivers. This was a qualitative study using in-person and telephone interviews with English-speaking transgender youth (12–24 years old), with and without their caregivers. Interviews were conducted using a semi-structured interview guide and transcribed verbatim. Statements from interviews were coded by theme. Recruitment ended when thematic saturation was reached, determined by investigators. 16 patients and 16 caregivers completed interviews. Overall, participants indicated no connection between transitioning and oral health. Many reported abandoning self-care, including oral health practices. Patients and caregivers alike did not prioritize disclosing transition-related information with oral health providers, despite uncertainty on the effects of related treatments on the oral cavity. At a time when transitioning youth may be in contact with health care providers more frequently and may be more inclined to share transition related details with them, the healthcare provider is uniquely positioned to encourage improved oral health emphasis and outcomes.